2011
DOI: 10.1039/c1cp21404g
|View full text |Cite
|
Sign up to set email alerts
|

Structural models for yttrium aluminium borate laser glasses: NMR and EPR studies of the system (Y2O3)0.2–(Al2O3)x–(B2O3)0.8−x

Abstract: The structure of laser glasses in the system (Y(2)O(3))(0.2){(Al(2)O(3))(x))(B(2)O(3))(0.8-x)} (0.15 ≤ x ≤ 0.40) has been investigated by means of (11)B, (27)Al, and (89)Y solid state NMR as well as electron spin echo envelope modulation (ESEEM) of Yb-doped samples. The latter technique has been applied for the first time to an aluminoborate glass system. (11)B magic-angle spinning (MAS)-NMR spectra reveal that, while the majority of the boron atoms are three-coordinated over the entire composition region, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…Thus, we estimate the fraction of four-coordinated boron ( [4] B) in this glass system from the literatures. According to the earlier reports [24], 2Y 2 O 3 -5B 2 O 3 -3Al 2 O 3 glass similar composition to our glass contains 12% of [4] B. In the case of 2.5La 2 O 3 -5B 2 O 3 -2.5Al 2 O 3 , the amount of [4] B is about 11% [15].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we estimate the fraction of four-coordinated boron ( [4] B) in this glass system from the literatures. According to the earlier reports [24], 2Y 2 O 3 -5B 2 O 3 -3Al 2 O 3 glass similar composition to our glass contains 12% of [4] B. In the case of 2.5La 2 O 3 -5B 2 O 3 -2.5Al 2 O 3 , the amount of [4] B is about 11% [15].…”
Section: Discussionmentioning
confidence: 99%
“…4 that can frequently be disentangled by a two-dimensional pulsed EPR technique called hyperfine sublevel correlation spectroscopy (2D-HYSCORE). [25][26][27][28] While some qualitative studies on crystalline and glassy laser host materials have shown the general feasibility of this approach, [29][30][31][32][33] no work on rare-earth doped fluoride phosphate glasses has been reported so far, to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 95%
“…The above pulsed EPR methods present a new approach to rare‐earth‐doped luminescent glasses . Figure shows results for a series of 25BaF 2 –25SrF 2 –(30− x )Al(PO 3 ) 3 – x AlF 3 −19.75YF 3 −0.25YbF 3 glasses.…”
Section: The Current State Of the Art: New Insight Into Medium‐range mentioning
confidence: 99%
“…[79][80][81][82][83][84][85][86] The above pulsed EPR methods present a new approach to rare-earth-doped luminescent glasses. 73,87,88 Figure 15 shows results for a series of 25BaF 2 -25SrF 2 -(30Àx)Al (PO 3 ) 3 -xAlF 3 À19.75YF 3 À0.25YbF 3 glasses. Here, the electron spins associated with the paramagnetic Yb 3+ ions serve as the spies of their electronic and nuclear environments.…”
Section: Rare-earth Environments In Photonic Glasses Studied By Cormentioning
confidence: 99%